Pengaruh Kinerja Keuangan, Asimetri Informasi, dan Manajemen Laba terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di BEI Tahun 2020-2022 - Rizqullazid Mufiddin; Dharmayanti Pri Handini; Nasharuddin Mas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of financial performance proxy Debt to Equity Ratio, information asymmetry, and earnings management on stock prices in banking sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The method used in this study is an explanatory method with a quantitative approach. While for the sampling technique itself using purposive sampling with a selected sample of 34 companies. For research analysis, namely using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. From the results of the study, it can be concluded that financial performance with the Debt to Equity Ratio proxy does not have a significant partial effect on stock prices, information asymmetry has a negative and significant partial effect on stock prices, earnings management does not have a significant partial effect on stock prices, and financial performance, information asymmetry, and earnings management do not significantly affect stock prices simultaneously.